2013
DOI: 10.1073/pnas.1304332110
|View full text |Cite
|
Sign up to set email alerts
|

Insights into insect wing origin provided by functional analysis of vestigial in the red flour beetle, Tribolium castaneum

Abstract: Despite accumulating efforts to unveil the origin of insect wings, it remains one of the principal mysteries in evolution. Currently, there are two prominent models regarding insect wing origin: one connecting the origin to the paranotal lobe and the other to the proximodorsal leg branch (exite). However, neither hypothesis has been able to surpass the other. To approach this conundrum, we focused our analysis on vestigial (vg), a critical wing gene initially identified in Drosophila. Our investigation in Trib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
149
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(165 citation statements)
references
References 35 publications
15
149
0
Order By: Relevance
“…Previous work in beetles revealed that the prothorax (T1) contains vgdependent tissue, leading to the proposal that the affected T1 regions represent wing serial homologs (18,37). Our present results show that, in addition to vg, several other genes involved in wing development also have a function in the wingless prothorax of Oncopeltus.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Previous work in beetles revealed that the prothorax (T1) contains vgdependent tissue, leading to the proposal that the affected T1 regions represent wing serial homologs (18,37). Our present results show that, in addition to vg, several other genes involved in wing development also have a function in the wingless prothorax of Oncopeltus.…”
Section: Discussionsupporting
confidence: 59%
“…No such effects were previously observed in beetles (18,37), possibly because radical reconfiguration of the thorax during the pupal state in holometabolous insects may override any such effects. In Oncopeltus vg RNAi adults, the scutellum lost its tip, and its distinct triangular morphology was changed to a shield-like shape (Fig.…”
Section: Insights About Wing Origins and Functionalization From T1 Ecmentioning
confidence: 81%
See 3 more Smart Citations